2004
DOI: 10.1007/s00414-004-0434-7
|View full text |Cite
|
Sign up to set email alerts
|

Forensic age estimation in living subjects: the ethnic factor in wisdom tooth mineralization

Abstract: Radiological assessment of the mineralization stage of third molars is a major criterion for age estimation of living people involved in criminal proceedings. To date insufficient knowledge has been obtained about how the ethnic origin can influence tooth mineralization. A comparative study of wisdom tooth mineralization was carried out on three population samples: one German, one Japanese and one South African. To this end, 3,652 conventional orthopantomograms were evaluated on the basis of Demirjian's stages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
138
1
25

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 249 publications
(178 citation statements)
references
References 15 publications
10
138
1
25
Order By: Relevance
“…For the remaining age groups of 17 to 22, the mean value for stage H did not change in comparison to all age groups (15)(16)(17)(18)(19)(20)(21)(22). The mean value for stage D however increased considerably by almost 2 years from 16.4 to 18.2 (see Table 3, stage D).…”
Section: Significance Of Mean Valuesmentioning
confidence: 81%
See 2 more Smart Citations
“…For the remaining age groups of 17 to 22, the mean value for stage H did not change in comparison to all age groups (15)(16)(17)(18)(19)(20)(21)(22). The mean value for stage D however increased considerably by almost 2 years from 16.4 to 18.2 (see Table 3, stage D).…”
Section: Significance Of Mean Valuesmentioning
confidence: 81%
“…Olze et al [15] were able to show an influence of ethnicity on mineralization of the wisdom teeth for stages D-F for Japanese and D-G for South Africans. For stage H, an ethnic influence could neither be proven nor disproven.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, when considering the timing of fusion of secondary ossification centers throughout the skeleton researchers have discovered that rates for such events can be affected by the sex of the individual and their ancestry and birth century (Crowder & Austin 2005, Cunha et al 2009, Scheuer & Black 2004). However, others have cited differences in the environment and social economic status for differences in maturation rates (Saunders et al 1993, Olze et al 2004, Langley-Shirley & Jantz 2010, Shirley & Jantz 2011, Vucic et al 2014. Furthermore, due to the more fragile nature of immature bone and destructive taphonomic processes, as well as inadequate recovery techniques, non-adult individuals may only be partially represented (Gordon & Buikstra 1981, Pokines & De La Paz 2016Walker et al 1988.…”
Section: Subsection One: Age Estimationmentioning
confidence: 99%
“…Wisdom tooth mineralization has been the main criterion used for dental age diagnosis in adolescents so far. Olze et al [13] studied the effects of ethnicity on wisdom tooth mineralization. To summarize, the authors concluded that their Caucasoid population ranked in the middle of the investigated ethnic groups in terms of dental development as defined by their age at reaching the large majority of mineralization stages.…”
Section: Introductionmentioning
confidence: 99%